Novel troponin-like biomarkers of acute kidney injury - Emad Abdallah; Emam Waked; Bassam Al-Helal; Reem Asad; Malak Nabil; Tarek Harba (Saudi Journal of Kidney Diseases and Transplantation, 2013)
Acute kidney injury (AKI) is a common and serious condition in both the inpatient and outpatient settings, and its diagnosis depends on serum creatinine measurements. Unfortunately, creatinine is a delayed and unreliable indicator of AKI. The lack of early biomarkers has limited our ability to translate promising experimental therapies to human AKI. Fortunately, understanding the early stress response of the kidney to acute injuries has realized a number of potential biomarkers. For example, neutrophil gelatinase-associated lipocalin is emerging as an excellent stand alone troponin-like biomarker in the plasma and urine for predicting and monitoring clinical trials and in the prognosis of AKI. In recent years, a number of new biomarkers of AKI with more favorable test characteristics than creatinine have been identified and studied in a variety of experimental and clinical settings. This review will consider the most well-established biomarkers of AKI.